2012
DOI: 10.1128/mbio.00220-11
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Inflammatory Responses Provoked by Pneumococcal Sialidase

Abstract: Cell surface expression of sialic acid has been reported to decrease during immune cell activation, but the significance and regulation of this phenomenon are still being investigated. The major human bacterial pathogen Streptococcus pneumoniae causes pneumonia, sepsis and meningitis, often accompanied by strong inflammatory responses. S. pneumoniae expresses a sialidase (NanA) that contributes to mucosal colonization, platelet clearance, and blood-brain barrier penetration. Using wild-type and isogenic NanA-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 73 publications
3
46
0
Order By: Relevance
“…For example, NanA remodels mucosal cell surface glycoproteins to promote bacterial colonization of the upper respiratory tract (11,12) and contributes to pulmonary inflammation along with the development of SPN pneumonia (13,14). However, the host has adapted to counteract the pathological effects of this SPN virulence factor by the clearance from blood circulation of host factors bearing AMR ligands that have been unmasked by NanA desialylation.…”
mentioning
confidence: 99%
“…For example, NanA remodels mucosal cell surface glycoproteins to promote bacterial colonization of the upper respiratory tract (11,12) and contributes to pulmonary inflammation along with the development of SPN pneumonia (13,14). However, the host has adapted to counteract the pathological effects of this SPN virulence factor by the clearance from blood circulation of host factors bearing AMR ligands that have been unmasked by NanA desialylation.…”
mentioning
confidence: 99%
“…Our hypothesis and results could be extended over other exogenous co-infections in HIV-infected people with agents containing NA; for example, Streptococcus pneumoniae [19,20] or Trypanosoma cruzi. [21] Moreover, without any regard to HIV infection, it has been reported that a number of sialylated Gps and glycolipids can be desialylated in vivo by interaction with endogenous cellular NAs, thus changing their function.…”
Section: Resultsmentioning
confidence: 86%
“…CbpA binds to the cerebral endothelial laminin receptor and platelet-activating factor receptor [5,6], and those interactions induce pneumococcal invasion into the host brain. NanA, which localizes on bacterial cell surfaces by its cell-wall anchoring motif, activates hBMECs via its lectin-like domain and increases pneumococcal invasion into hBMECs [7,8]. Therefore, it was considered important to assess pneumococcal cbpA and nanA expressions of the Δ ccs4 strain.…”
Section: Resultsmentioning
confidence: 99%